Mednarodni projekt o količini in kakovosti v zdravstveni negi - Filej, Bojana (Obzornik zdravstvene nege, 2001)
The article describe an ongoing project on quantity and quality in nursing care that takes place at the Health Centre Maribor in cooperation with the Katholic University of Nijmegen and which is financed by Ministry for Foreign Affairs from the Netherlands MATRA. The article presents results of research on quantity and quality in nursing care in primary health care settings.
Keywords: mednarodni projekti; zdravstvena nega